Energy Consumption and Government Policy in Addressing the Rising Fuel Oil Prices - Istiqomah, Nurul; Mafruhah, Izza; Wilyawati, Arieska Kurnia; Mayasari, Febi; Salleh, Norlida Hanim Mohd (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
This study aims to determine the effect of economic growth, per capita income, world oil prices and the amount of subsidies on energy consumption in Indonesia both in the short and long term. As well as knowing the policies carried out by the government to overcome the increase in fuel prices. The data used is secondary data from 1972 - 2022 and analyzed using ECM Domowitz-El Badawi and Atlas.ti which is used to organize, explore and analyze data on policies made by the government to overcome rising fuel prices. The analysis shows that economic growth, per capita income and the size of subsidies have a long-run effect on energy consumption, while world oil prices have both a short and long-run effect on energy consumption. The reduction of subsidies that caused fuel prices to increase had both positive and negative effects on society, and the government made several policy efforts to overcome the turmoil that existed in the community. Among them are adjusting fuel prices and prices of other affected goods, limiting ownership of motorized vehicles, maintaining a stable supply of fuel in the long term and increasing supervision and enforcement in fuel abuse.